Good and bad sides of the Italian Presidency of the Council of the European Union in the second half of 2014 (Economic and Political Thought, 2015)
From 1 July to 31 December 2014, Italy held the Presidency of the Councilof the European Union for the seventh time in the history of the EuropeanCommunities. The Presidency took place in a very difficult period in thehistory of integration: the economic and financial crisis of the Eurozone wasnot overcome, there were tensions in the relations with Russia in connectionwith the situation in the east of Ukraine, there was a threat resulting fromthe unstable situation in the Mediterranean and there were changes in themost important posts of the European institutions after the elections to theEuropean Parliament. The main priorities of the Italian Presidency, alsoadopted by the presidency trio with Latvia and Luxemburg, focused on thepro-growth policy in economy, completion of the development of the bankingunion in the financial area and active foreign policy, the main elementsof which was solidarity in the Mediterranean policy (combating illegalimmigration), emphasising strategic relations with Russia, reviving economicrelations with the countries of Asia and the Pacific and economic relationswith the United States. Due to Italy’s internal weakness reflected in unstablepolitical situation and economic crisis, the Presidency managed to implementonly some of the plans. It was the Presidency that mostly passed unnoticed.